THE INFLUENCE OF SEA-LEVEL CHANGES ON SEA-BOTTOM MORPHOLOGY OF SINGKAWANG WATERS WEST KALIMANTAN BASED ON ANALYSES OF BATHYMETRIC AND SEISMIC DATA - Hananto Kurnio; Noor C.D. Aryanto (Marine Geological Institute of Indonesia, 2011)
In the history of Quaternary geology, global climate changes influenced worldwide sea-level variations. On this study, these phenomena are tried to be assessed through sea-bottom morphology changes using bathymetric and seismic strata box data obtained during field survey in Singkawang Waters, West Kalimantan. Sea-level changes in this area are referred to global variations that had been studied by many researchers. Maximal depth attained during bathymetry mapping was -52 meters which take place as a depression between Lemukutan and Penata Besar Islands. General depths are - 30 m; thus, morphology reconstruction was done for sea-level positions - 10 m, - 20 m, and - 30 m from mean sea level. At the study area, sea-level dropped more than -30 m was only occurred in sea bottom morphology of isolated depressions. These isolated depressions are assumed as paleo-lakes which occurred throughout Sunda Land by some authors. The study also shows that sea-level history in Singkawang’s area span from approximately 10,000 years ago or Holocene time to Recent. During low sea-levels, the sea-bottom morphology was characterized by more extension of Singkawang land, formations of narrow straits between islands and developments of paleo-lakes assumed as fresh water lakes in the past. These events, based on Voris’s Diagram, occurred about 10,200 up to 8,300 years ago. On the other hand, marine clays appeared on coastal area of Singkawang. These might be evidence of sea-level rise in this area. About + 5m sea-level rise flooded this area approximately 4,200 years ago. Influences of sea-level changes to subbottom geological conditions were also assessed. The assessment was carried out by analyzing shallow seismic reflection records by using strata box. The records demonstrated that subsurface geology were characterized by truncation reflector configurations interpreted as fluvial environments. Keywords : sea-level changes, sea-bottom morphology, bathymetry, strata box, Singkawang Waters, West Kalimantan. Dalam sejarah geologi Kuarter, perubahan iklim global mempengaruhi variasi permukaan laut di seluruh dunia. Pada kajian ini fenomena tersebut dicoba dipelajari melalui perubahan morfologi dasar laut menggunakan data batimetri dan seismik pantul dangkal yang diperoleh selama survei lapangan di Perairan Singkawang, Kalimantan Barat. Perubahan muka laut di daerah ini mengacu pada variasi global yang telah dikaji oleh beberapa peneliti. Kedalaman tertinggi yang diperoleh selama pemetaan batimetri adalah 52 meter, yaitu berupa suatu daerah depresi antara Pulau Lemukutan dan Penata Besar. Umumnya kedalaman adalah -30 m; sehingga, rekonstruksi morfologi dilakukan pada posisi muka laut - 10 m, - 20 m, dan -30 m dari muka laut rata-rata. Di daerah kajian, muka laut turun lebih dari - 30 m hanya terjadi dalam morfologi dasar laut yang berupa daerah-daerah depresi yang terisolasi. Morfologi depresi terisolasi ini diduga sebagai danau purba oleh beberapa penulis yang terdapat pada Daratan Sunda. Kajian ini juga menunjukkan bahwa sejarah muka laut di daerah Singkawang mulai dari sekitar 10.000 tahun lalu (Holosen) hingga saat ini (Resen). Selama turunnya muka laut, morfologi dasar laut dicirikan oleh semakin meluasnya daratan Singkawang, terbentuknya beberapa selat sempit dan berkembangnya danau-danau purba yang diduga sebagai danau air tawar di masa lalu. Peristiwa tersebut, berdasarkan diagram umur terhadap muka laut Voris, terjadi sekitar 10.200 hingga 8.300 tahun lalu. Sementara itu, keterdapatan lempung endapan laut dari data pemboran pantai di Singkawang merupakan bukti naiknya muka laut di daerah ini. Kenaikan muka laut sekitar + 5 m telah menggenangi daerah ini kira-kira 4.200 tahun lalu. Tulisan ini juga membahas tentang pengaruh perubahan muka laut terhadap kondisi geologi bawah dasar laut. Kajian dilaksanakan dengan menganalisa rekaman seismik pantul dangkal. Rekaman menunjukkan bahwa geologi bawah dasar laut dicirikan oleh konfigurasi reflektor ’toreh dan isi’ atau truncation yang ditafsirkan sebagai lingkungan fluvial. Kata kunci : perubahan muka laut, morfologi dasar laut, batimetri, strata box, Perairan Singkawang, Kalimantan Barat.